Does malnutrition inflammation score maintains its predictive risk assessment in the modern hemodialysis era? - Martins, VS (2020)
Abstract Background and Aims Malnutrition Inflammation score (MIS) is a risk score published in 2001 (Kalantar-Zadeh, 2001) and validated in 2008 (Rambod, 2009). It is associated with a high mortality and morbidity risk in hemodialysis (HD) patients (pts). Currently, HD pts population is composed of much older individuals, submitted to a high efficient treatment with access to pharmacological and nutritional therapy, assured by a bundled payment, when comparing with the validation study population. The objective of this study is to evaluate if MIS maintain its predictive risk assessment. Method Cross sectional analysis of HD pts from 25 outpatient clinics. MIS was evaluated at the study baseline. Univariable and multivariable Cox additive regression models were used to analyze the data. C-index was estimated to assess the performance of the final model. A level of significance of = 0.05 was considered. Results A total of 2444 pts were analyzed (59.0% males; 32.0% diabetic) during a median period of 48 months (P25=31; P75=48), 875 patients registered MIS<5, corresponding to 35.8%. All-cause mortality was observed in 860 pts (35.2%). There were 202 (35.8%) events in the group of patients with MIS<5, while in the group with MIS5, the number of deaths was higher (658 pts, 41.9%). In univariable analysis using Cox additive model, the main results were: In multivariable analysis, adjusting for age, nPNA, IDWG, Kt/V and diabetes, a MIS 5 and 7 showed, respectively, a HR of 1.761 (IC 95%, p<0.001) and 1.822 (IC 95%, p<0.001). Conclusion The findings of this analysis confirms that MIS maintains a discriminative power to identify higher risk of mortality. In this model, age and diabetes also correlate with mortality risk increase, while nPNA, IDWG and Kt/V have the opposite effect.